Impaired decidualization caused by downregulation of circadian clock gene BMAL1 contributes to human recurrent miscarriage†. Issue 1 (15th April 2019) - Lv, Shijian; Wang, Na; Ma, Jin; Li, Wei-Ping; Chen, Zi-Jiang; Zhang, Cong
Abstract: Recurrent miscarriage (RM) is characterized by two or more consecutive losses of a clinically established intrauterine pregnancy at early gestation. To date, the etiology of RM remains poorly understood. Impaired decidualization is thought to predispose women to subsequent pregnancy failure. The transcriptional factor brain and muscle aryl hydrocarbon receptor nuclear translocator-like (BMAL1) controls circadian rhythms and regulates a very large diversity of physiological processes. BMAL1 is essential for fertility. Here, we investigated the expression and function of BMAL1 in human decidualization and its relation with RM. A total of 39 decidua samples were collected. We also examined human endometrial stromal cells (HESCs) and primary endometrial stromal cells (ESCs), and primary decidual stromal cells (DSCs) isolated from decidua of first-trimester pregnancies. Compared to normal pregnant women, the expression of BMAL1 was reduced in the decidual tissues from individuals with RM. After in vitro induction of decidualization, the transcription of BMAL1 in both HESCs and primary ESCs was increased. This is in line with the relatively higher expression of BMAL1 in DSCs than in ESCs. Silencing of BMAL1 resulted in impaired decidualization. Moreover, levels of tissue inhibitors of metalloproteinases (TIMPs) increased significantly upon decidualization. Further experiments demonstrated that BMAL1 silencing curtails the ability of DSCs to restrict excessive trophoblast invasion via downregulation of TIMP3. Our study demonstrates a functional role for BMAL1 during decidualization: the downregulation of BMAL1 in RM leads to impaired decidualization and aberrant trophoblast invasion by regulating TIMP3 and consequently predisposing individuals for RM. Abstract : Downregulation of BMAL1 in human recurrent miscarriage (RM) leads to impaired decidualization and aberrant trophoblast invasion by regulating TIMP3 and consequently predisposing individuals for RM.